Effect of different carbonization of activated carbon produced from oil palm shell in adsorption of Liquefied Petroleum Gas (LPG) - Herawan, Safarudin Gazali; Ayob, Md Razali (2009)
The effects of material precursor selections in the quality of activated carbon produced from oil palm shell, an abundant palm-oil mill solid waste, were studied. Scanning Electron Microscopy (SEM) was used to analyze the micropore and surface condition of activated carbon. Simple gravimetric model was developed to test LPG adsorption rate of produced sample. The result indicates that material size was essential to develop uniform pore size of activated carbons. However, too small material precursor size would cause low yield and macropore during pyrolysis and activation, respectively. The pore distributions had a significant effect on the amount of LPG adsorbed in low pressure (2 bar).